2018
DOI: 10.1007/s00339-018-1995-5
|View full text |Cite
|
Sign up to set email alerts
|

Impact of ablation time on Cu oxide nanoparticle green synthesis via pulsed laser ablation in liquid media

Abstract: Large-scale commercial production of nanoparticles via efficient, economical, and environmentally friendly methods is a challenging endeavour. The laser ablation method being a green and potential route of nanoparticles synthesis can be exploited to achieve this end. In this work, we report the ablation of a copper target submerged in distilled water by pulsed Nd:YAG laser. The influence of ablation time on the structure and optical properties of grown copper oxide nanoparticles are studied. Such nanoparticle … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 24 publications
3
12
0
Order By: Relevance
“…Compared to the initial composition of Vitreloy 1, the element O is additional, and its atomic ratio exceeds 20%, which most probably stems from the confined water or its vapor. This result demonstrates that the ablation products experience an oxidation reaction due to the high-temperature-and-pressure (HTP) environment during the underwater PLA [33].…”
Section: Resultsmentioning
confidence: 87%
See 1 more Smart Citation
“…Compared to the initial composition of Vitreloy 1, the element O is additional, and its atomic ratio exceeds 20%, which most probably stems from the confined water or its vapor. This result demonstrates that the ablation products experience an oxidation reaction due to the high-temperature-and-pressure (HTP) environment during the underwater PLA [33].…”
Section: Resultsmentioning
confidence: 87%
“…detected because of its low atomic mass. As mentioned above, the additional high-concentration of the element O results from the laser-assisted chemical reaction between nanoparticles and confined water or its vapor [33]. For the core-shell nanoparticles in Fig.…”
Section: Resultsmentioning
confidence: 87%
“…In addition, the crystal lattice planes (‐220), (11‐3) and (‐111) of monoclinic structure of CuO phase corresponding to the interplanar spacing of 0.13 nm, 0.15 nm and 0.27 nm respectively were also observed. The presence of single phase CuO NPs can be attributed to the high chemical reactivity of Cu atoms with the surrounding medium at high temperature during prolonged laser ablation process . The presence of both Cu/CuO phases indicates that the synthesised NPs are polycrystalline in nature which is in line with the obtained UV‐Vis spectra of the sample.…”
Section: Resultsmentioning
confidence: 98%
“…Synthesis of nanoparticles (NPs) and the investigation of their size dependent optical and structural properties have become important areas of research in nanoscience and nanotechnology. Among metal and semiconductor NPs, copper, gold, silver and their oxide NPs have attracted global attention during the last decades due to their vast potential in the field of medical and optical applications. This is because of their exceptional optical, electronic and catalytic properties.…”
Section: Introductionmentioning
confidence: 99%
“…The effects of ablation time on the structure and optical properties of the grown copper oxide nanoparticles were investigated. The results of transmission electron microscopy images showed that the synthesized nanoparticles were spherical with an average size of 24-37 nm [273]. In 2018, S. Yu et al presented a new strategy for producing TiO 2 or TiO 2 /carbon microstructures using the DLW process.…”
Section: Laser Equimentmentioning
confidence: 99%